Biological and chemical composition of pomegranate fruit grown in Azerbaijan and Uzbekistan (Texas Journal of Agriculture and Biological Sciences, 2022)
In the collections, 69 varieties of pomegranate were taken into account. But in farms specializing in Uzbekistan are planted mostly bitter and Kazakh pomegranate lot, picky pomegranate, red pomegranate, white pieces, ulfi and b. varieties are also widely scattered